Screening Packaging and Biologically Active Cushioning Materials for Postharvest Storage of Litchi - Alam, Masood; Singh, J P; Yadav, S K; Siddiqui, M W (Journal of Postharvest Technology, 2014)
Keeping litchi fruits in its own leaves during marketing is a common practice that provides postharvest protection to the fruits from weight and colorloss. Considering this common practice, the present experiment was carried out to evaluate different combinations of cushioning and packaging materials for enhanced shelf-life and fruit quality of litchi. The results revealed that the litchi fruits stored without stalks in CFB boxes, cushioned with green cassia (Cassia alataL.) leaves recorded the best postharvest quality throughout the storage. The treatment was found the most effective in curtailing physiological loss in weight, browning, and acidity with higher retention of TSS. The fruits kept with stalks in CFB boxes, cushioned with green cassia leaves ranked second in merit, however, it was found effective in reducing spoilage loss of fruitswith higher values of total sugars and ascorbic acid. Begusarai, East and West Champaran and Bhagalpur districts.